2017
DOI: 10.3892/or.2017.5942
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with neutrophils promotes gastric cancer cell migration and invasion by inducing epithelial-mesenchymal transition

Abstract: Emerging evidence has revealed that neutrophils have phenotypic and functional plasticity. Neutrophils could be polarized towards a pro-tumor phenotype by tumor-derived factors. In the present study, we investigated the role of the interaction with neutrophils on the functions of gastric cancer cells in vitro. Human promyelocytic leukemia HL-60 cells were induced to differentiate into neutrophil-like cells (HL-60N) using dimethyl sulfoxide (DMSO). Human gastric cancer cells were co-cultured with HL-60N cells o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 23 publications
1
41
0
Order By: Relevance
“…In a gastric cancer microenvironment, macrophages via interaction with mesenchymal stem cells induce differentiation of cancer-associated fibroblasts (CAFs) [232][233][234]. CAFs are crucial in the initiation, growth, and migration properties of gastric cancer cells [235,236]. They are responsible for the release of carcinogenic and proinflammatory factors including interleukin-6 (Il-6), cyclooxygenase-2 (COX-2), chemokine (C-X-C motif) ligand 1 (Cxcl1), chemokine (C-X-C motif) ligand 9 (Cxcl9), interferon gamma-induced protein 10 (Cxcl10), stromal cell-derived factor 1 (Cxcl12), and fibroblast-specific protein 1 (FSP1), which promote the EMT process and induce carcinogenesis, promoting migration and invasion [237][238][239].…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%
“…In a gastric cancer microenvironment, macrophages via interaction with mesenchymal stem cells induce differentiation of cancer-associated fibroblasts (CAFs) [232][233][234]. CAFs are crucial in the initiation, growth, and migration properties of gastric cancer cells [235,236]. They are responsible for the release of carcinogenic and proinflammatory factors including interleukin-6 (Il-6), cyclooxygenase-2 (COX-2), chemokine (C-X-C motif) ligand 1 (Cxcl1), chemokine (C-X-C motif) ligand 9 (Cxcl9), interferon gamma-induced protein 10 (Cxcl10), stromal cell-derived factor 1 (Cxcl12), and fibroblast-specific protein 1 (FSP1), which promote the EMT process and induce carcinogenesis, promoting migration and invasion [237][238][239].…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%
“…In this study, infiltration of plasma cells was also shown to prolong survival in gastric cancer as a component of the humoral immune response, consistent with previous studies (18,19); however, the precise role of these cells remains poorly understood. Neutrophils were assigned the highest coefficient in our risk assessment formula, possibly due to their ability to regulate many of the malignancy-associated behaviors of cancer cells, such as migration and invasion (20,21). The difference in infiltration ratio among these four immune cell types may be correlated with leukocyte migration-related pathways, which were enriched in our high risk subgroup; a high risk score was indicative of infiltrates with a high proportion of neutrophils and low proportions of plasma cells, activated CD4 + memory T cells, and Tfh cells.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil-cancer cell interaction can lead to the polarization of neutrophils towards a pro-tumor phenotype [101]. found that bone marrow neutrophils in mice activated by GC cells promote their ability to migrate, thus leading to increased invasiveness.…”
Section: Bone Marrow Neutrophilsmentioning
confidence: 99%
“…Cancer-associated fibroblasts (CAFs) have been shown to have a crucial influence on the initiation, growth, and migration of tumor cells [101]. This is especially due to the reduced cell-to-cell adhesion, enhanced mobility, and constant activation [87,105].…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation